ANALISIS DEIKSIS CERPEN REMBULAN DI MATA IBU KARYA ASMA NADIA - Nuraeni, Lia; Siagian, Irwan; Hasanah, Uswatun; Astuti, Yulia Dini; Nugroho, Rudiyanto Sapto (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Deixis is included in the study of pragmatics which is a link between the structure of language and the context of the situation used. The use or phenomenon of deixis usually appears in dialogs between characters in literary works including short stories. The research entitled "Deixis Analysis of Short Story "Rembulan Di Mata Ibu" by Asma Nadia" aims to examine the use of deixis in the short story "Rembulan Di Mata Ibu" by Asma Nadia. This study focuses on five kinds of deixis, including social deixis, time deixis, discourse deixis, persona deixis, and place deixis. In analyzing the data, the researcher uses pragmatic analysis method with qualitative-descriptive technique. The data underlying this research are words, sentences, or dialogs that have the use of deixis in them, both social deixis, discourse deixis, time deixis, persona deixis, and place deixis. The stages in analyzing the use of deixis are the stages of reading short stories, recording data, identifying, classifying, analyzing, formulating, and presenting data. The data analysis shows that there are social deixis, time deixis, discourse deixis, persona deixis, and place deixis found in the short story "Rembulan Di Mata Ibu" by Asma Nadia.